Menggali Paradoks: Yesus Bangkit dan Yesus Dibangkitkan - Egidius Agu; Gregorius Tri Wardoyo (JURNAL PASTORAL KATEKETIK, 2024)
This research aims to explore the paradox within Christian belief regarding the resurrection of Jesus Christ: Jesus rose and Jesus was raised. This exploration is crucial given that the resurrection of Jesus is the foundation of Christian faith, which understands His victory over death, while also symbolizing resurrection and the hope of eternal life. This study is examined through the perspective of biblical theology. By gaining a deeper understanding of the paradox of Jesus' resurrection, it is hoped that it will provide richer insights into theological understanding and enrich academic discussions as well as the comprehension of the content of faith. The points that reconcile the paradox of the resurrection affirm that Jesus is truly God and truly human, emphasize the relationship of the Triune God, and highlight the uniqueness of His resurrection. The use of the terms "rose" and "was raised" affirms the two natures in one person, Jesus Christ